Financial Stress, Financial Literacy, Counselling and the Risk of Homelessness - Adam Steen; David MacKenzie (Australasian Accounting, Business and Finance Journal, 2013)
Poor financial literacy may lead to poor life choices. These life choices can create or contribute to financial stress with adverse consequences - not the least of which may be homelessness. These issues are relatively well understood, but there is limited research on the link between financial stress, financial literacy and counselling, and homelessness. Specifically, there has been little research on how improved financial literacy and appropriate financial counselling might help to prevent homelessness. This paper synthesises existing literature on this topic and considers these issues using the ABCX family stress model of Hill (1958) using data from an Australian program aimed at alleviating family homelessness, the Home Advice Program. We provide evidence that suggests that case management and support which incorporates financial counselling and financial literacy can assist in moderating the impact of financial stress and help those at risk of homelessness. The findings have implications for public policy in the areas of financial education, consumer finance, and social services provision.
Keywords: Financial stress; Financial literacy; Homelessness